Regional Anthropometry Changes in Antiretroviral-Naı¨ve Persons Initiating a Zidovudine-Containing Regimen in Mbarara, Uganda - Thompson, Vanessa; Medard, Bitekyerezo; Taseera, Kabanda; Chakera, Ali J.; Andia, Irene; Emenyonu, Nneka; Hunt, Peter W.; Martin, Jeffrey; Scherzer, Rebecca; Weiser, Sheri D.; Bangsberg, David R.; Tien, Phyllis C. (AIDS research and human retroviruses, 2011)
Lipodystrophy is commonly reported in Africa after antiretroviral therapy (ART) is initiated, but few studies have objectively measured changes in body composition. Body composition was determined in 76 HIV-infected participants from Mbarara, Uganda after starting a thymidine-analog regimen, and annual change was determined using repeated measures analysis. We measured skinfolds (tricep, thigh, subscapular, and abdomen), circumferences (arm, hip, thigh, waist), and total lean and fat mass (using bioelectric impedance analysis). A cross-sectional sample of 49 HIV-uninfected participants was studied for comparison. At baseline, most body composition measures were lower in HIV-infected than uninfected participants, but waist circumference was similar. After 12 months on ART, there was little difference in body composition measures between HIV-infected and uninfected participants; median waist circumference appeared higher in HIV-infected participants (79 vs. 75 cm; p¼0.090). Among HIV-infected participants, increases were observed in total lean and fat mass, circumference, and skinfold measures; only the increase in tricep skinfold did not reach statistical significance (þ1.05mm; 95% confidence interval: _0.24, 2.34; p¼0.11). Regional anthropometry in peripheral and central body sites increased over 12 months after ART initiation in HIV-infected persons from southwestern Uganda, suggesting a restoration to health. Gains in the tricep skinfold, a reliable marker of subcutaneous fat, appeared blunted, which could indicate an inhibitory effect of zidovudine on peripheral subcutaneous fat recovery
Keywords: Lipodystrophy; Antiretroviral therapy; Body composition; HIV-infected